Prevalence of 20210 A Allele of the Prothrombin Gene in Venous Thromboembolism Patients - Leroyer, Christophe; Mercier, Bernard; Oger, Emmanuel; Chenu, Eric; Abgrall, Jean-François; Férec, Claude; Mottier, Dominique (Thrombosis and Haemostasis, 1998)
Background. The 20210 A allele variation in the 3’ -untranslated region of the prothrombin gene was recently identified as a risk factor as regards deep venous thrombosis. Aim. To assess the frequency of the variation in unselected patients with a proven venous thromboembolism (VTE). Methods. The presence of the prothrombin variation was determined in all consecutive patients referred from July 1994 to August 1997 for a clinical suspicion of VTE, and in whom the diagnosis was confirmed. A control group consisted of bone marrow volunteer donors. Results. Of the 366 patients included, 17 (4.6%) were carriers of the 20210 A allele (95% CI, 2.4% to 6.7%). The mutation was present in 1.0% of the 400 controls. Odds ratio for having VTE in the presence of the 20210 A allele was 4.8 (95% CI, 1.5 to 19.8). Forty-six (12.5%) patients had the mutation of the factor V gene and five (1.4%) patients shared both mutations. After excluding the carriers of the factor V mutation, odds ratio for having VTE in the presence of the 20210 A allele was 3.7 (95% CI, 1.1 to 13.6). Mean age at admission as well as mean age of the first VTE episode were both significantly higher in patients free from the two mutations studied, as compared to carriers of the 20210 A allele (p = 0.04 and 0.01, respectively). Conclusion. Our findings in a large series of patients (1) confirm the 20210 A allele prothrombin gene as a risk factor for VTE. (2) suggest that its association with the factor V Leiden is not uncommon.